Pharmacy undergraduates’ willingness to communicate (WTC) and its relationship with language learning motivation - Nor Jasni, Nudiya Idswa Binti; Safian, Syahidatul Akmar Binti (AJELP: Asian Journal of English Language and Pedagogy, 2021)
This study aimed at investigating the willingness to communicate (WTC) in English among Pharmacy undergraduates in various contexts. The study also aimed to see the relationship between WTC in English and the respondents’ language learning motivation. The data for this study was extracted from 75 Pharmacy undergraduates who have undergone their practical sessions at selected pharmacies by using a questionnaire. The study opted for a quantitative method and the questions asked were adapted from McCroskey (1992) and Lambert’s Attitude Motivation Test Battery (1987) to collect the respondents’ responses. Based on the overall score, it is clear that Pharmacy undergraduates are less willing to communicate in English despite being exposed to it since primary school. However, they are keen to communicate in English on specific situations such as when they are surrounded with familiar acquaintances. Nevertheless, the Pharmacy undergraduates have a high level of language learning motivation due to the importance of the language use for their career.